Continuing education in nursing as a factor associated with knowledge on breastfeeding - Mariana de Oliveira Fonseca-Machado; Vanderlei José Haas; Juliana Cristina dos Santos Monteiro; Flávia Gomes-Sponholz (Universidad de Antioquia, 2014)
Objective. Identifying the knowledge about breastfeeding of the nurses of the Family Health Program, and possible associations between the knowledge and personal, professional and self evaluation aspects. Methodology. Observational and cross-sectional study conducted in family health units of a city in Minas Gerais, Brazil, with 85 nursing professionals. Data were collected through a questionnaire. We used the Student t-test for differences between means and Pearson correlation analysis. Results. The mean score of the professionals on the knowledge test was 6.6 and was higher in the group that attended courses on breastfeeding. Conclusion. There is a need for continuing education, providing reflective and critical mobilization, the questioning of reality and identification of users needs.